Transcranial direct current stimulation (tDCS) as an adjunct intervention in stroke rehabilitation - Allman, C (2012)
Stroke is the leading cause of physical disability worldwide and patients are often left with substantial impairments in motor function. Intensive physiotherapy is the most widely used rehabilitative intervention following a stroke, but the potential for motor recovery with physiotherapy alone is limited by the activity of the residual cortex. Consequently there is increasing interest in combining traditional rehabilitation techniques with adjunct interventions to improve outcomes. Transcranial direct current stimulation (tDCS) is a promising tool for rehabilitation. Anodal stimulation of primary motor cortex increases cortical excitability and in stroke patients this translates into transient behavioural improvements after a single session of stimulation. This thesis aimed to investigate whether repeated sessions of tDCS delivered in conjunction with an intensive motor training program would result in long-lasting improvement of motor abilities in chronic stroke patients. Twenty-four patients received motor training for two weeks for the paretic upper limb; patients were randomised to receive anodal or sham tDCS and were then examined over the subsequent three months to investigate behavioural improvements. All patients experienced a significant improvement in motor function following the motor training intervention. Patients who had received anodal tDCS experienced additional behavioural improvements that were more enduring over time. Baseline characteristics such as the presence of motor evoked potentials in the paretic hand and lesion volume were found to be significantly associated with initial motor impairment, and the degree of initial impairment and allocation to the anodal tDCS condition was found to predict therapy-mediated improvements in motor function. The results presented in this thesis provide important information regarding the improvement in motor abilities associated with repeated sessions of tDCS, and in particular they suggest that tDCS may be utilised as a clinically useful tool for motor rehabilitation in chronic stroke. Furthermore, they suggest that baseline characteristics could be used to target interventions to patients most likely to benefit.